Beyond Parental Conflicts: Reconstructing Child Custody Decisions Through Maslahah Mursalah - Lailul Ilham; Muhammad Zainuddin Sunarto; Muhammad Iqbal (Yayasan Lembaga Studi Makwa, 2026)
This study aims to reconstruct child custody decisions in Indonesia through the perspective of Maslahah Mursalah by examining the extent to which parental conflicts influence judicial determinations and affect the realization of the best interests of the child. Child custody disputes often arise from competing parental claims following divorce, creating legal and practical challenges for judges in determining custody arrangements that genuinely prioritize child welfare. The research employs a normative juridical methodology using statutory, conceptual, and case approaches. Primary legal materials consist of Indonesian family law regulations, judicial decisions concerning child custody, and classical and contemporary Islamic legal sources discussing Maslahah Mursalah. Secondary materials include scholarly articles, books, and legal commentaries relevant to child welfare and Islamic family law. The findings demonstrate that child custody decisions in Indonesia are frequently influenced by formal legal considerations and parental rights claims, while the child’s long-term physical, emotional, educational, and social interests may receive insufficient attention. The analysis further reveals that Maslahah Mursalah offers a comprehensive framework that enables judges to move beyond rigid legal formalism and parental conflicts by focusing on the protection and welfare of children as the primary objective of custody determinations. This approach emphasizes the prevention of harm (mafsadah) and the realization of benefit (maslahah) in accordance with the broader objectives of Islamic law. The study concludes that Maslahah Mursalah can serve as a normative foundation for reconstructing child custody decisions in Indonesia toward a more child-centered and welfare-oriented model. Academically, this research contributes to the development of contemporary Islamic family law by integrating the principle of the best interests of the child with Islamic legal reasoning, thereby providing an alternative framework for judicial decision-making and future reforms in child custody law and practice.